Improved control of childhood asthma with low‐dose, short‐term vitamin D supplementation: a randomized, double‐blind, placebo‐controlled trial. Issue 7 (2nd March 2016) - Tachimoto, H.; Mezawa, H.; Segawa, T.; Akiyama, N.; Ida, H.; Urashima, M.
Abstract: Background: In our prior randomized trial on preventing influenza, asthma attacks as a secondary outcome occurred less often in the vitamin D group than in the placebo group. We aimed to clarify whether low‐dose, short‐term vitamin D supplementation, in addition to standard treatments, improves control of childhood asthma. Methods: We conducted a randomized, double‐blind, placebo‐controlled trial comparing vitamin D3 supplements (800 IU/day) with placebo for 2 months in schoolchildren with asthma. The primary outcomes were frequency and severity of asthma judging from changes in asthma control levels defined by the Global Initiative for Asthma (GINA) by collaborating doctors at 2 and 6 months. Results: Japanese schoolchildren with asthma ( n = 89) were randomly assigned to receive vitamin D ( n = 54) or placebo ( n = 35). At 2 months, GINA asthma control was significantly more improved in the vitamin D group compared with the placebo group ( P = 0.015). Childhood asthma control test (CACT) scores, a secondary outcome, were also significantly ( P = 0.004) improved in the vitamin D group compared with the placebo group at 2 months, and differences remained significant ( P = 0.012) at 6 months. The proportion of patients with a peak expiratory flow rate <80% predicted was significantly less in the vitamin D group (8/54: 15%) than in the placebo group (12/35: 34%) at 6 months ( P = 0.032). Conclusions: Low‐dose, short‐term vitamin D supplementation in addition to standard treatment may improve levels of asthma control in schoolchildren.